First experiences with the New Enterprise2 (R) stent - Herweh, Christian; Nagel, Simon; Pfaff, Johannes; Ulfert, Christian; Wolf, Marcel; Bendszus, Martin; Möhlenbruch, Markus Alfred (Clinical neuroradiology, 2018)
IntroductionStent-assisted coiling of wide-necked intracranial aneurysms has become an established treatment and has significantly benefited from the introduction of compliant, self-expanding devices, such as the Enterprise VRD (EP-VRD). We report our experiences with the successor model, the Enterprise2 (EP2) stent in stent-assisted coiling as well as in the treatment of atherosclerotic stenosis.Materials and MethodsIn 11 consecutive patients 12 EP2 were used to treat 9 intracranial aneurysms and 2 stenoses.ResultsAll stents could easily be delivered including partial or complete recapturing when necessary. In two cases with sharp angled curves in the carotid siphon there was kinking and flattening of the stent resulting in incomplete wall apposition of the stent. Moreover, when vascular anatomy showed curves with angles >50° it was regularly observed that the proximal stent markers were asymmetrically arranged along the vessel circumference without influence on the stent apposition. Both findings could be reproduced in a silicone flow model.ConclusionThe EP2 performed well in our small patient cohort; however, above a critical acute angle there may be incomplete wall apposition of the stent.